2022
DOI: 10.3346/jkms.2022.37.e81
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Clinical Evaluation of an Artificial Intelligence Screening Method for Early Detection of STEMI in the Emergency Department

Abstract: Background Rapid revascularization is the key to better patient outcomes in ST-elevation myocardial infarction (STEMI). Direct activation of cardiac catheterization laboratory (CCL) using artificial intelligence (AI) interpretation of initial electrocardiography (ECG) might help reduce door-to-balloon (D2B) time. To prove that this approach is feasible and beneficial, we assessed the non-inferiority of such a process over conventional evaluation and estimated its clinical benefits, including a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…In terms of CAD, previous studies have demonstrated the feasibility and fine performance of AI-ECG models as a rapid screening tool for ACS in patients presenting with acute chest pain [ 6 - 8 ]. Although various model structures with different AI algorithms have been used, these models have focused on the prediction of ACS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of CAD, previous studies have demonstrated the feasibility and fine performance of AI-ECG models as a rapid screening tool for ACS in patients presenting with acute chest pain [ 6 - 8 ]. Although various model structures with different AI algorithms have been used, these models have focused on the prediction of ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there may be difficulties in applying these AI-ECG models in daily clinical practice, as additional software may be required for input signal transformation. In comparison, the QCG analyzer allows 12-lead ECG image data as input, extracting wave signals and vectorizing them through the initial encoding step [ 5 , 6 ]. Previous reports have validated the consistent performance of the QCG analyzer for printed ECG images and ECG photographs obtained as screenshots from a smartphone [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Preliminary evidence has shown the diagnostic capability of STEMI through AI-based ECG analysis to be comparable to that of a skilled cardiologist, potentially allowing for reductions in cardiac catheterization laboratory activation time and door-to-balloon time. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Some of these challenges may be mitigated through the development of AI capable of analyzing ECG image outputs. 6 9 Nonetheless, the diversity in shape and format of pre-hospital ECG outputs, combined with the high risk of contamination, hampers the direct application of these algorithms to real-world data. Therefore, creating an AI solution that can accurately interpret pre-hospital ECG data to inform the risk of STEMI would represent a significant technological advancement in this field.…”
Section: Introductionmentioning
confidence: 99%